Introductory Comments to a Press Conference on the Judgement Striking Down the Sign Law - Johnson, William (1999)

Brief Presented to the Standing Committee on Education, Government of Quebec - The English Speaking Catholic Council (ESCC) (1999)
The English Speaking Catholic Council (ESCC) made a major act of good faith when in May 1988, at the National Assembly Hearings studying Bill 107 (the Education Act), it defended its brief in favor of the reorganization of school boards along linguistic lines while strongly advocating measures to ensure the confessional character of schools

Alliance Quebec Condemns Louise Beaudoin's Assertion that Quebec Civil Servants Could Serve Immigrants and Allophones in French Only - Alliance Quebec (AQ) (1999)

Alliance Quebec Goes At Last to Court to Force the Government to Approve Long Overdue English Health Services - Alliance Quebec (AQ) (1999)

An Outlaw Government - Alliance Quebec (AQ) (1998)

Speech to the St. James Literary Society - Johnson, William (1998)

Alliance Quebec Demands that People Receive Health and Social Services in the Language They Choose to Use - Alliance Quebec (AQ) (1997)

Alliance Quebec Worried About Federal-Provincial Manpower Talks - Alliance Quebec (AQ) (1996)